Efektivitas Pelayanan Kesehatan di Puskesmas Akle Kabupaten Kupang Ditinjau dari Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan - Adinda Devita Sulastri Dima; Saryono Yohanes; Hernimus Ratu Udju (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Akle Health Center of Kupang Regency always strives to serve the community well.well in all care needs including curative services(treatment), preventive (prevention efforts), promotive (health improvement)and rehabilitation (health restoration) with the hope that patients who obtain health services feel satisfied with the services provided.The purpose of this study is to determine the effectiveness of health services at the Akle Health Center, Kupang Regency, and to find out the inhibiting factors for the effectiveness of health services at the Akle Health Center, Kupang Regency. The type of research conducted is empirical juridical research. The types and sources of data used are primary and secondary data. Primary data is data obtained directly from the research location through direct interviews with respondents and based on researcher observations.Secondary data is data obtained from literature studies.Data analyzed descriptively qualitative. The results of this study indicate that: (1) The Effectiveness of Health Services at Puskesmas Akle Kupang Regency are: (a) Implementation of Health Services at Puskesmas Akle Kupang Regency, (b) Implementation of Preventive Health Services, (c) Implementation of Promotive Health Services, (d) Implementation of Curative Health Services, (e) Implementation of Rehabilitative Health Services. (2) Factors inhibiting the effectiveness of health services at the Akle Health Center, Kupang Regency are: (a) Human Resources, (b) Infrastructure Facilities, (c) System factors, Procedures and Regulations, (d) Skills.